Diasporic cold warriors nationalist China, anticommunism, and the Philippine Chinese, 1930s-1970s - Kung, Chien-Wen 1981- (Studies of the Weatherhead East Asian Institute, Columbia University, 2022)
"Explains how and why the Philippine Chinese became the most ardent overseas Chinese supporters of the Kuomintang during the Cold War. This book argues for a networked and diasporic understanding of the KMT-ROC party-state. Ties between the Philippine Chinese, the ROC, and the Philippines were constitutive of an intra-Asian anticommunist ecumene: a Cold War waged not by the United States and not only by states but by Asian countries and peoples working with each other"-